2018
DOI: 10.1590/2175-8239-jbn-3781
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of clinically validated primary causes of end-stage renal disease (ESRD) in a State Capital in Northeastern Brazil

Abstract: The data contradicted national studies reporting primary hypertension as the main cause of chronic kidney disease (CKD). A high rate of unknown causes and categorization bias were observed mainly in relation to primary hypertension as a cause of CKD, which affects the overall prevalence of causes of ESRD in patients on dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0
8

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 7 publications
2
10
0
8
Order By: Relevance
“…In this perspective, our results have demonstrated that serum and salivary levels of calcium, urea, and creatinine exhibit significant statistical differences (p<0.001). Our findings are consistent with previous studies [2,[29][30][31][32], adding to the existing data to support the possibility of employing analysis of salivary creatinine and urea for the diagnosis and assessment of CRF [33].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this perspective, our results have demonstrated that serum and salivary levels of calcium, urea, and creatinine exhibit significant statistical differences (p<0.001). Our findings are consistent with previous studies [2,[29][30][31][32], adding to the existing data to support the possibility of employing analysis of salivary creatinine and urea for the diagnosis and assessment of CRF [33].…”
Section: Discussionsupporting
confidence: 92%
“…Concerning age, our findings demonstrated that most patients had an age greater than or equal to 40 years old, which corroborates the results of some studies [5,12,24,25]. In Brazil, the prevalence of CRF is high; approximately 11 to 22 million adults are estimated to have some degree of renal dysfunction in a population of about 200 million and 70% of the adult population [2]. In the Brazilian Northeast exist 134 dialysis units, and our study corresponded to approximately 3% of this totality.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In these cases, renal biopsy is an important method to confirm the etiology of this glomerular disease 2 . In Brazil, data regarding trends in glomerular and nonglomerular nephropathies confirmed by means of a renal biopsy are still limited to certain regions of the country [3][4][5][6] or based on sampling from hospitals/ nephrology centers 3,5,[7][8][9][10][11][12][13] . In Santa Catarina, there are no population data that can contribute to a better epidemiological understanding of the prevalence of nephropathies diagnosed through renal biopsy.…”
Section: Abstract Introductionmentioning
confidence: 99%
“…In the multivariate analysis, among the primary glomerulopathies, males had a higher risk for the occurrence of IgAN [OR=2.02; 95% CI 1. 13…”
mentioning
confidence: 99%